2011 Conference Record of the Forty Fifth Asilomar Conference on Signals, Systems and Computers (ASILOMAR) 2011
DOI: 10.1109/acssc.2011.6190070
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhanced multi-rate iLBC

Abstract: The internet Low Bit-rate Codec (iLBC) inherently possesses high robustness to packet loss which is one of the essential properties of Voice over Internet Protocol (IP) applications. Another important feature is the rate flexibility, which allows the speech codec to adapt its bit rate to constantly changing network condition. Previously, the multi-rate operation of the iLBC was enabled by utilizing the Discrete Cosine Transform (DCT) and entropy coding. In this paper, various approaches to improve performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…We introduced the different approach to add rate flexibility to the iLBC in [14] by employing the discrete cosine transform (DCT) and entropy coding to encode the start state. The schemes which improve multi-rate iLBC were presented in [15]. However, the simulation results showed that speech quality was saturated toward the higher bit rate.…”
Section: Introductionmentioning
confidence: 93%
“…We introduced the different approach to add rate flexibility to the iLBC in [14] by employing the discrete cosine transform (DCT) and entropy coding to encode the start state. The schemes which improve multi-rate iLBC were presented in [15]. However, the simulation results showed that speech quality was saturated toward the higher bit rate.…”
Section: Introductionmentioning
confidence: 93%